Botulinum toxin: Intercurrences and complications in the application (Research, Society and Development, 2023)
The search for beauty and rejuvenation has become a widely discussed subject in today's society, both by women and men. In this context, treatment with botulinum toxin has gained prominence in aesthetics due to its durability and low occurrence of side effects. Botulinum toxin, a neurotoxin produced by a gram-positive anaerobic bacterium, has seven different serotypes, with botulinum toxin A being the most used for aesthetic purposes. Wrinkles are the result of repetitive contractions of certain muscles, and botulinum toxin A acts by reducing muscle tension, being indicated for various aesthetic procedures, such as shaping the eyebrows and nose, smoothing dynamic wrinkles on the forehead, lifting the corners of the mouth and correcting of facial asymmetries. However, it is important to emphasize that any aesthetic procedure presents risks, and it is essential that professionals have a broad anatomical, muscular and subcutaneous knowledge of the face, in addition to precise manual skills. Although it is considered a relatively simple and safe procedure, the use of botulinum toxin requires adequate care. This work aims to address the intercurrences and complications associated with the application of botulinum toxin, aiming to provide guidance to specialists and promote an aesthetic treatment with a minimum of adverse events.